Novos processos de realização e circulação no longa-metragem brasileiro Castanha - Reque, Cristiane Scheffer (2017)
This dissertation studies the Brazilian audiovisual marketplace between 2012 and 2015 based on the relationship between different modes of production and distribution of domestic films. The main focus is on the production process behind the film Castanha (Davi Pretto, Rio Grande do Sul, 2014), analyzing each phase of production by comparing it to another contemporary film with different characteristics, such as the director's experience, budget size, screenplay development, and its regional location within Brazil. The references follow the guidelines of the triad method (BARONE, 2009), which defines the audiovisual field through its three main activities: production, distribution and exhibition. The analysis is constructed through the perspective of the cinematic fact (COHEN-SÉAT, 1946; METZ, 1980), considering aspects related to what happened before, during and after the film and its encounter with the public. The main objective is to look at certain production aspects of Castanha in comparison to the production of the film Reaching for the moon (Bruno Barreto, Rio de Janeiro, 2013), its distribution in comparison to Rat Fever (Cláudio Assis, Pernambuco, 2012), and its exhibition in comparison to the path taken by The second mother (Anna Muylaert, São Paulo, 2015), and through this analysis noting asymmetries and similarities in the production and distribution of recent domestic feature films. Based on data made available by Ancine and Filme B, it is possible to look beyond the market figures, questioning the validity of box office rankings as the only parameter for measuring a film’s success. This study considers concepts that vary from Chris Anderson’s long tail to the Latin American scenario of Canclini and Martín-Barbero, including studies of the Brazilian marketplace by Butcher, Gatti, Chalupe, Régio, as well as Barone. Finally, this dissertation offers elements that contribute to the discussion around the exhibition paths taken by Brazilian films with niche qualities, both in traditional movie theaters and outside of them.